2011
DOI: 10.4103/0259-1162.84177
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative testing in elective surgery: Is it really cost effective?

Abstract: Introduction:During preoperative preparation, patients undergo investigations to detect asymptomatic diseases. The probability of finding significant abnormalities on such routine investigations is small, and these investigations unnecessarily increase costs of perioperative care. We evaluated current practices, compliance with national guidelines and costs of preoperative investigations at the National Hospital of Sri Lanka (NHSL).Materials and Methods:Patients undergoing elective surgery at the general surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
10
0
6
Order By: Relevance
“…The present study shows similar, if not worse, findings as compared to the study done in Srilanka. [ 20 ] The mentioned study found very poor compliance to the local recommendations for CXRs, coagulation profiles, liver enzymes and 2D ECHO. Another retrospective review found that 100% of the patients had many routine investigations done, but there was no change in the plan of anaesthesia in any of these cases despite having 32.5% abnormal test results for some of the tests.…”
Section: Discussionmentioning
confidence: 95%
“…The present study shows similar, if not worse, findings as compared to the study done in Srilanka. [ 20 ] The mentioned study found very poor compliance to the local recommendations for CXRs, coagulation profiles, liver enzymes and 2D ECHO. Another retrospective review found that 100% of the patients had many routine investigations done, but there was no change in the plan of anaesthesia in any of these cases despite having 32.5% abnormal test results for some of the tests.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that these less experienced anaesthesiologists and surgeons might be more likely to request unnecessary preoperative tests. 11 Lastly, the majority of patients who attend higher-level facilities, such as IALCH, are complex cases that require specialised care. 12 These patients are likely to have existing mild-to-severe systemic disease (ASA grade II-IV), which would automatically qualify them for routine preoperative U&E testing according to the NICE preoperative testing guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…One of the areas which has been scrutinised from time to time is the usefulness of routine pre-operative laboratory testing as a part of pre-operative assessment. [ 1 2 ] The task forces of the American Society of Anesthesiologists (ASA) and National Institute of Clinical and Health Excellence (NICE) have provided guidance on the use of pre-operative laboratory tests before elective surgeries for last one and half decades. [ 3 4 ] The current evidence and guidance recommend against the practice of routine pre-operative laboratory tests.…”
Section: Introductionmentioning
confidence: 99%